Hepatopulmonalni sindrom - Dajčman, Davorin (Medicinski razgledi, 2001)
Hepatopulmonary syndrome is caused by intrapulmonary vasodilation that leads to abnormal arterial gas exchange in the setting of liver disease or portal hypertension. Hepatopulmonary syndrome results in hypoxemia due to pulmonary vasodilatation with significant arteriovenous shunting and ventilation-perfusion mismatch. It is the most widely recognized of the processes associated with end-stage liver disease and is seen in up to 15% of cirrhotics. Testing for the presence of oxygenation abnormalities and intrapulmonary vasodilation is needed to make the diagnosis. Chronic liver dysfunction is associated with pulmonary manifestations due to alternations inthe production or clearance of circulating cytokines and other mediators. Excess production of nitric oxide in the lung contributes to pulmonary vasodilation. Hepatopulmonary syndrome is an increasingly common indication for liver transplantation because no medical therapies are established as effective.
Keywords: Hepatopulmonalni sindrom; Hepatopulmonary syndrome; jetrne bolezni; zapleti; pljučne bolezni